Polymorphism E23K KCNJ11 Gen as a Risk Factor of Diabetes Mellitus in Serawai Tribe Of Bengkulu - Raden Sunita; Sahidan Sahidan; Rachmat Hidayat; Resva Meinisasti (HM Publisher, 2020)
ABSTRACT Background: Type 2 diabetes mellitus (T2DM) is a multifactorial disease involving genetic and environmental factors. The E23K KCNJ11 gene polymorphism causes KATP canal overactivity, decreases cell membrane depolarization potential, and decreases insulin secretion. E23K polymorphism of the KCNJ11 gene as a risk factor for T2DM. Research Objective: This study aimed to analyze the E23K polymorphism of the KCNJ11 gene as a risk factor for T2DM in the Bengkulu Serawai. Method: This study is a case-control study. The subjects of the study were 100 people with T2DM patients as a case group (50 people) and Non-DM subjects with families who did not have a history of T2DM as a control group (50 people). Fasting blood glucose (GDP) was analyzed by spectrophotometry and E23K KCNJ11 gene by polymerase chain reaction fragment length polymorphism (PCR-RFLP). Data were analyzed by statistics. Results: The frequency of AA genotypes in cases was higher than the controls (12% and 8%) (p = 0.001). The frequency of A allele in the case was higher than the control (32% and 18%) (p = 0.017). The risk of T2DM on AA / GA genotypes was 4.75 times higher in cases than controls (p = 0,000, OR 4.75 95% CI 2.01-11.24). The risk of T2DM in A allele was 2.14 times higher in cases than in controls (p = 0.017, OR 2.14, 95% CI 1.11-4.15). Conclusion: E23K polymorphism of the KCNJ11 gene as a risk factor for T2DM in Bengkulu Serawai Tribe. Keywords: E23K gene KCNJ11, DMT2, Non-DMT2.